Synthesis of 5-[alkoxy-(4-nitro-phenyl)-methyl]-uridines and study of their cytotoxic activity - Brulíková, Lucie; Dzubák, Petr; Hajdúch, Marián; Lachnitová, Lenka; Kollareddy, Madhusudhan; Kolár, Milan; Bogdanová, Katerina; Hlavác, Jan (European journal of medicinal chemistry, 2010)
A series of uridine analogues modified at the 5-position with the 5-[alkoxy-(4-nitrophenyl)-methyl] moiety was synthesized. Nucleosides were formed as a mixture of two diastereoisomers, which were separated and tested for their cytotoxic activity in vitro against different cancer cell lines and for antimicrobial activity. Relationships between structure and the above mentioned activities were studied. The cytotoxic activity was slightly increased in some cases by transformation of bases to nucleosides. Depending on the length of the alkyl chain increased cytotoxic and antimicrobial activity were noted. The cytotoxic activity of the nucleosides was not due to cell cycle alterations, DNA and/or RNA synthesis.
Keywords: uridin; lidé; Antineoplastic Agents; protinádorové látky; inhibiční koncentrace 50; Cell Line, Tumor; Bacteria; Inhibitory Concentration 50; nádorové buněčné linie; Uridine; Humans